The Influence of Organizational Culture and the Role of Internal Audit on Fraud Prevention - Panatap, Josua (Dinasti Publisher, 2024)
The rise of fraud or fraud that occurs in organizations can cause losses to the organization so that the organization is difficult to develop, so there is a need for awareness of the importance of fraud prevention to minimize losses due to fraud. This article aims to examine and review research related to the factors that influence fraud prevention, namely organizational culture and the role of internal audit. This literature review also has the aim of developing hypotheses about the influence between variables to be used in further research. The results of this research article conclude that organizational culture, and the role of internal audit have a positive effect on fraud prevention. This indicates that the better the organizational culture and internal audit, the better the implementation of fraud prevention in the organization